Studyholism and Attachment Style: A Study among Italian University Students - Yura Loscalzo; Marco Giannini (Behavioral Sciences)
Studyholism (or obsession with studying) is a new potential clinical condition introduced in the literature in 2017. Since then, growing research has supported its conceptualization as a clinical disorder and highlighted some potential intervention targets, namely trait worry, social anxiety, negative interpretation bias, and defense mechanisms. The present study aims to extend the literature concerning psychodynamic-related constructs that might constitute targets for interventions aimed at reducing Studyholism by investigating the role of attachment in 1073 students (Mage = 23.48 ± 3.77), balanced concerning civil status (i.e., currently being single or involved in a relationship/non-single). Among the main findings, we found that insecure attachment—mainly preoccupied attachment—is a positive predictor of Studyholism in both non-single and single students. However, there are also some differences depending on the civil status. Finally, (single) disengaged studyholics have a statistically significant lower level of secure attachment than (single) engaged studyholics. In conclusion, this study showed the value of distinguishing between non-single and single students when investigating the role of attachment. Regarding problematic overstudying specifically, the study provided support for its definition as a clinical disorder, also with evidence of the appropriateness of its OCD-related conceptualization. Finally, it suggests preoccupied (insecure) attachment as a target to reduce Studyholism by fostering in students the feeling of being loved and deserving of being loved in their current adult relationships.